Implementation of Early Warning System on SMART VU SCADA PT PLN (Persero) With LED Warning Lights - Fadil, M .; Muskhir, Mukhlidi (Departemen Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2024)
Electric power distribution is a crucial element in meeting the needs of the community, especially in the workshop and electronic equipment repair sector. The transmission process aims to optimize efficiency and reduce power losses. PT PLN (Persero) UP2D SUMBAR has a high commitment in responding to the needs of the community, related to the distribution of electricity, especially in the 20 KV distribution network. Although it already uses two Early Warning Systems connected to SMART VU SCADA, the DCC room alarm sound is disabled to minimize noise. Therefore, this research focuses on implementing an additional Early Warning System with LED warning lights. The research methodology includes literature study, initial testing (Experimental Method), system design, hardware design, second testing (successful/unsuccessful), direct testing in the DCC room, and analysis of results. It is expected that this research can improve alarm notifications, speed up dispatcher response time, and increase vigilance in handling disturbances in the 20 KV distribution network.